MEDIASI PENAL DALAM PENYELESAIAN PERKARA KEKERASAN DALAM RUMAH TANGGA - Ni Kadek Ayu Ismadewi; Widodo.T Novianto; Hartiwiningsih (HUKUM PEMBANGUNAN EKONOMI, 2017)
AbstractThe purpose of this article  to determine the judge’s considerations using penal mediation in the settlement of Domestic Violence (KDRT) cases and its formulation in the future. This is a normative study with case approach, comparative approach and conceptual approach. The legal matterial of this research are primary legal matterial and secondary legal material with deductive analystic mind. Reffering the research above, Showed that there is a difference of judges consideration using the result of penal mediation in the form of peace between offender and victim who still have relationship of husband and wife in the settlement of case of domestic violence for offense. First, it is based on the benefit and recovering of the relationship of the offender and the victim, to the exclusion of the legalistic rules, so that the Judge arrives at the decision of the prosecution otherwise unacceptable. Second, based on expediency, but the legal process continues with the imposition of a conditional penalty. The existence of differences in consideration and judgment because the mediation of penal itself is not yet regulated in positive criminal law in Indonesia. However, with the starting point on the principle of benefit and the theory of pragmatic realism, the Judge should not worry or hesitate to use the results of peace in penal mediation as a way of resolving a domestic violence case by  stopping the proceedings, although considered to be contrary to the principle of legal certainty. This has implications for the achievement of substantial justice for offender and victim, a quicker settlement of cases and avoid the accumulation of cases in the Court. Therefore the future needs to be formulated for mediation of penal entry into inseparable part in the procedure of settling the case of domestic violence, especially for offense complaints, ranging from the level of investigation, prosecution and court.Keywords: Penal Mediation; Domestic Violence; Judge’s DecisionAbstrakTujuan artikel ini adalah untuk mengetahui pertimbangan Hakim menggunakan mediasi penal dalam penyelesaian perkara Kekerasan Dalam Rumah Tangga (KDRT) dan formulasinya di masa mendatang. Penelitian ini merupakan studi normatif dengan pendekatan  kasus, pendekatan komparatif dan pendekatan konseptual. Bahan hukum yang digunakan berupa bahan hukum primer dan bahan hukum sekunder dengan pola analisis deduktif. Hasil penelitian, menunjukkan bahwa adanya perbedaan pertimbangan Hakim menggunakan hasil mediasi penal berupa perdamaian antara pelaku dan korban yang masih ada hubungan suami istri dalam penyelesaian perkara KDRT untuk delik aduan. Pertama, mendasarkan pada kemanfaatan dan pulihnya hubungan pelaku dan korban, dengan mengenyampingkan aturan yang bersifat legalistik, sehingga Hakim sampai pada putusan berupa penuntutan dinyatakan tidak dapat diterima. Kedua, mendasarkan pada kemanfaatan, namun proses hukum tetap dilanjutkan dengan penjatuhan pidana bersyarat. Adanya perbedaan pertimbangan dan penjatuhan putusan tersebut karena mediasi penal sendiri memang belum diatur dalam hukum positif pidana di Indonesia. Akan tetapi dengan bertitik tolak pada asas kemanfaatan dan teori realisme pragmatis, semestinya Hakim tidak khawatir atau ragu menggunakan hasil perdamaian dalam mediasi penal sebagai jalan penyelesaian perkara KDRT dengan menghentikan proses perkara, meski dianggap bertentangan dengan asas kepastian hukum. Hal tersebut berimplikasi pada tercapainya keadilan substansial bagi pelaku dan korban, penyelesaian perkara yang lebih cepat dan menghindari penumpukan perkara di Pengadilan. Kedepannya perlu diformulasikan agar mediasi penal masuk menjadi bagian tidak terpisahkan dalam prosedur penyelesaian perkara KDRT, khususnya untuk delik aduan, mulai dari tingkat penyidikan, penuntutan dan pengadilan.Kata kunci: Mediasi Penal; Kekerasan Dalam Rumah Tangga; Putusan Hakim.